Tax Revenue Losses through Cross-Border Loss Offset: An Insurmountable Hurdle for Formula Apportionment - Mohammed Mardan; Michael Stimmelmayr (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper analyzes the relevance of firm losses for tax revenues and welfare when switching from separate accounting to a system of tax base consolidation with formula apportionment. We find that a system change unambiguously decreases tax revenues in the short run, in which neither firms nor governments can adjust their behavior, due to the cross-border loss offset inherent to formula apportionment. In the medium run, in which only firms can adjust their strategies, tax revenues are still lower under formula apportionment if the probability of incurring losses or the costs of profit shifting are sufficiently small. However, in the long run, where both firms and governments are able to adjust their behavior after the system change, a switch from separate accounting to formula apportionment is beneficial under the aforementioned conditions. Furthermore, we show that a higher weight of input shares in the apportionment formula may mitigate tax competition because, contrary to output factors, input factors provide an insurance against tax revenue shortfalls due to loss-making affiliates.
Keywords: H73; H25; F23; 330; separate accounting; formula apportionment; corporate losses; cross-border loss offset; CCCTB